Hydromorphism - Its Definition and Correlation between Three Major Classification Systems with Reference to West Africa - Okusami, T. A. (Faculty of Agriculture, University of Ife, 2015)
Hydromorphic soils may be defined simply as any wetland soil that will not support crops (or plants), with aerobic edaphic requirements, during the peak of the groundwater recharge. The influence of the water-table is largely controlled by the texture of the profile. This is of significance because the capillary fringe of any water-table may be as saturated as those horizons under the water-table, and this tends to increase the height of the groundwater. A depth of 100 cm. to a saturated zone is suggested as the depth below which a pedon ceases to become aquic or show features associated with hydromorphism that could limit the environment to anaerobic crops. For a general landuse purpose, a probable depth of 150 cm. is suggested as the depth beyond which a pedon ceases to become hydromorphic. Because hydromorphism does not preclude those soil forming processes peculiar to the well-drained upland soils, classification as outlined in Soil Taxonomy (USDA) could be appropriate for the classification of hydromorphic soils. The aquic prefix points to the influence of the water regime on the pedogenesis and properties of the soils concerned. Attempt at correlating the three systems, viz. USDA, FAO - UNESCO and French was made.